The Mediating Role of Digital Literacy in the Relationship between Innovation Orientation and the Performance of Digital MSMEs in Indonesia's Creative Economy Ecosystem - Nelly Suryani; Tina Nurzachra (Eastasouth Institute, 2026)
The digitalization process has significantly accelerated the growth of digital Micro, Small, and Medium Enterprises (MSMEs) within Indonesia’s creative economy ecosystem. However, the role of digital literacy as a mechanism linking innovation orientation to MSME performance remains insufficiently explored, particularly from a phenomenological perspective. This study aims to explain and develop a conceptual model of the mediating role of digital literacy in the relationship between innovation orientation and the performance of digital MSMEs operating within Indonesia’s creative economy ecosystem. This research employed a qualitative approach using an interpretative phenomenological design grounded in the interpretivist paradigm. Data were collected through semi-structured, in-depth interviews with 15 participants involved in digital MSMEs, selected through purposive sampling. The data were analyzed using an inductive thematic analysis approach until thematic saturation was achieved. Four major themes emerged from the analysis: (1) the internalization of digital literacy as an innovation practice, (2) platform-based innovation orientation as an adaptive strategy, (3) the cognitive-practical mediating role of digital literacy in transforming innovation into performance outcomes, and (4) the socio-cultural ecosystem as a contextual moderator. The findings indicate that digital literacy effectively facilitates the translation of innovation orientation into tangible organizational outcomes. Digital literacy extends beyond a set of technical competencies and functions as a form of habitus that actively bridges innovation orientation and performance achievement among digital MSMEs. These findings contribute to the advancement of dynamic capability theory and Bourdieu’s habitus theory within the context of digital MSMEs in Indonesia’s creative economy, while also providing a foundation for future research.